Utilization of Social Media as a Marketing Tool for Startup Entrepreneurs (Case Study of Mpasi Tibiya in Cicalengka Bandung) - Suherman, Jajang; Andani, Riva; Sarusu, Armansyah M.; Kusnara, Hasti Pramesti; Rohmanto, Ricky; Mayanti, Yuni (International Journal of Linguistics, Communication, and Broadcasting, 2025)
Micro, Small, and Medium Enterprises play a strategic role in the Indonesian economy, particularly in creating jobs and encouraging innovation. One sector that continues to rapidly develop is the food and beverage business, including baby food. In this regard, social media has become an important tool that allows novice entrepreneurs to market their products more effectively and efficiently. Digitalization and technological development have changed the way business is conducted, including in marketing strategies. Social media provides a great opportunity for budding entrepreneurs to reach a wider audience without incurring high costs. In this context, the 'MPASI Tibiya' business uses platforms like Instagram and WhatsApp to promote their baby food products, which are designed to meet the nutritional needs of children aged 6 to 24 months. Marketing through social media allows MPASI Tibiya to build a closer relationship with consumers. Content such as daily menu information, customer testimonials, and visual promotions become effective tools to attract the attention of young mothers who are active in the digital world. With this approach, entrepreneurs not only expand the market but also create consumer trust in the quality of their products. However, the use of social media also presents various challenges. Increasingly tight competition in the digital world, changes in platform algorithms, and criticism from customers can become obstacles in building a positive image. Therefore, an engaging and adaptive content strategy is needed to face the continuously evolving market dynamics.